Architecture, Art, And Moderate Moralism - Caroll, Nöel (The Nordic Journal of Aesthetics, 2017)
In this essay Noël Carroll explores the question of whether a moral defect in a work of architectural art can ever also count as an aesthetic /artistic defect. Adopting the stance of a moderate moralist and mobilizing what has been called the “uptake argument,” he argues against the moderate autonomist that sometimes a moral defect in an architectural artwork can also be an aesthetic/artistic defect